Penerapan Media Pembelajaran Kartu Bilangan Pada Materi Satuan Waktu Untuk Meningkatkan Keberhasilan Belajar Siswa Kelas 3 MI - Arni, Yusni; Alhadi, Audia Maharani; Anggraini, Silfira; Isnaini, Gini Lailatul (LPPPI Publishing, 2024)
One of the problems that occur in the world of education in Indonesia is caused by learning factors that are not free and active so that the classroom atmosphere tends to be monotonous and the impact is that students are not motivated to participate in teaching and learning activities optimally. As a result, low learning motivation has an impact on the learning outcomes achieved, resulting in grades not reaching the KKM. Students are the learning subjects and the teacher is only a facilitator, with the existence of learning media, students will be able to create independence in understanding the material which will influence the learning outcomes they will obtain. The aim of this research is to find out how to implement number cards and the learning outcomes from implementing number cards in Mathematics with Time Unit material for grade 3 students at MI An-Nuur Palembang. The method used in this research used field research, which took place at MI An-Nuur Palembang, Sukarno Harjo Wardoyo, 7 Ulu, Seberang Ulu 1 District, Palembang City, South Sumatera, with a population of 22 grade 3 students, and a sample of all grade 3 students using a qualitative descriptive approach. Data collection techniques use observation, interview and documentation. The results of this research show that: (1) the implementation of number cards is a solution to the situation where students do not understand time unit material and (2) the implementation of number cards can improve mathematics learning outcomes.